THE PREVALENCE OF ESOPHAGEAL CANCER IN PATIENTS REFERRED TO JAMHURIAT HOSPITAL IN KABUL, AFGHANISTAN: A CROSS-SECTIONAL STUDY 2023 (British Journal of Global Ecology and Sustainable Development, 2024)
Background: Esophageal cancer (EC) is the 7th most common cancer in the world and the 6th cancer in terms of patient mortality. This cancer is caused by the abnormal growth of the tissues of the esophageal tube and is generally divided into two types: EAC and ESCC. Drinking alcohol, and smoking are the main risk factors for this cancer.Aim and method: This study aims to investigate the prevalence of EC in the patients of the Oncology Department of Jamhuriat Hospital in Kabul during 2023. This study is a retrospective cross-sectional descriptive study in which the required information was collected from the register of cancer patients in the Oncology Department of Jamhuriat Hospital in Kabul in 2023.Results: 82 EC patients were diagnosed in the Oncology Department of Jamhuriat Hospital in 2023. The prevalence of EC in patients referred to the Jamhuriat hospital was (1.82%). The majority of EC patients are between 41-60 years old (52.4%), male (82.9%), married (87.8%), Pashtun (46.3%), self-employed (78.8%), illiterate (43.9%), living in rural areas with low-income. The BMI of the majority of patients was normal, and (56.1%) of patients were treated with chemotherapy. (20.7%) patients had a family history of cancer, (57.3%) of patients were smokers, and the prevalence of EAC was higher than ESCC.Conclusion: EC is one of the most common cancers among those who refer to Jamhurit Hospital, the age of the patients is lower than in other countries, and the prevalence of this cancer is higher in rural areas. Public awareness and identification of aggravating factors of this cancer are the main necessary measures to prevent the further spread of this cancer.